Desafios da Avaliação na Educação Física escolar: contribuições para uma avaliação formativa - Garcia, Rafael Silva (2025)
This study discusses assessment in Physical Education school in light of the formative assessment proposal. Its objectives are to identify in the literature research and reflections on assessment processes being used in Physical Education classes in schools and, based on this, analyze the formative assessment proposal and its presence in the Physical Education school literature. This is a theoretical study that had academic literature as its research corpus. The narrative review technique was chosen on the topic of assessment in Physical Education school, and the theoretical framework is composed of authors who defend the narrative assessment proposal. This study concludes that learning assessment should be valued in all school subjects, including Physical Education, which is often disregarded even by teachers themselves. Despite conceptual divergences, these reflect the great difficulty faced by many educators in their assessment practice. Throughout this research, we found different assessment methods, and although each has its importance within education, we consider in this study the assessment aspects that concern student learning in relation to what is presented in the classroom, based on normative curricular documents that guide teachers' pedagogical practice in schools. Therefore, formative assessment presents itself as a primary approach to the teacher's pedagogical work, as it has the necessary characteristics for teachers to identify the constitution of student learning and, with that, enable reorganizations throughout the teaching-learning process.